Higher Education in the American West : Regional History and State Contexts - Goodchild, Lester F.; Jonsen, Richard W.; Limerick, Patty; Longanecker, David A.; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2014)
Higher Education in the American West: Regional History and State Contexts is the first comprehensive regional history of American higher education. It offers new historical research on how societal forces and state actions brought about the region's one thousand two hundred institutions of higher learning in 15 western states.
Keywords: Education; America -- History; School management and organization; School administration; Higher education; Education -- History; Social sciences; History of Education; Administration, Organization and Leadership; History of the Americas; Social Sciences, general